Improving Network Reliability with Traffic Steering Using Two ISP Links on Mikrotik Routers - Saputra, Herdian; Badri, Fawaidul; Saputri , Nanda; Sipahutar , Erwinsyah; Oktrison, Oktrison (PERFECT: Journal of Smart Algorithms, 2024)
Traffic Steering is an additional technique applied to network traffic especially when filtering, modification, or optimization is required. Network operators usually use traffic steering to expand the value of VAS or value-added service (value-added service that refers to additional services (content) based on existing telecommunication networks). This technique is applied so that the use of traffic from a link can be directed according to the client's needs and further maximize the functional use of the link itself. In general, the implementation of traffic steering is built based on three concepts, namely: NAT (Network Address Translation), Firewall RAW, and IP Routes. In this Traffic Steering implementation, the DSTNAT chain feature on the NAT firewall is used to direct access with the destination that has been set to a specific web server.